Immunotherapy of Cancer: Developments and Reference Points, an Unorthodox Approach. (January 2019) - Nikolaou, Michail; Nikolaou, Georgios; Digklia, Antonia; Pontas, Christos; Tsoukalas, Nikolaos; Kyrgias, George; Tolia, Maria
Oncology is currently a sector of medical science with accelerated progress due to rapid technological development, the advancement in molecular biology, and the invention of many innovative therapies. Immunotherapy partially accounts for this advance, since it is increasingly playing an important role in the treatment of cancer patients, bringing on a sense of hope and optimism through a series of clinical studies and cases with spectacular results. Immunotherapy, after the initial successes it experienced in the early 20th century, was forgotten after chemotherapy and radiotherapy prevailed and developed slowly in the background. Today, it is the new hope for cancer treatment, despite the unorthodox path it has followed. In this article, we study the course and key points of the discovery of immune-oncology from the oncologist's point of view. We also record the questions that have been posed about immunotherapy that sometimes lead to confusion or stalemate.